Photoelastic and finite element stress analysis reliability for implant-supported system stress investigation - Anna Gabriella Camacho Presotto; Cláudia Lopes Brilhante Bhering; Ricardo Armini Caldas; Rafael Leonardo Xediek Consani; Valentim Adelino Ricardo Barão; Marcelo Ferraz Mesquita (Universidade Estadual de Campinas, 2018)
Aim: To compare the reliability between photoelastic and finite element (FE) analyses by evaluating the effect of different marginal misfit levels on the stresses generated on two different implant-supported systems using conventional and short implants. Methods: Two photoelastic models were obtained: model C with two conventional implants (4.1×11 mm); and model S with a conventional and a short implant (5×6 mm). Three-unit CoCr frameworks were fabricated simulating a superior first pre-molar (P) to first molar (M) fixed dental prosthesis. Different levels of misfit (µm) were selected based on the misfit average of 10 frameworks obtained by the single-screw test protocol: low (<20), medium (>20 and <40) and high (>40). Stress levels and distribution were measured by photoelastic analysis. A similar situation of the in vitro assay was designed and simulated by the in silico analysis. Maximum and minimum principal strain were recorded numerically and color-coded for the models. Von Mises Stress was obtained for the metallic components. Results: Photoelasticity and FE analyses showed similar tendency where the increase of misfit generates higher stress levels despite of the implant design. The short implant showed lower von Mises stress values; however, it presented stresses around its full length for the in vitro and in silico analysis. Also, model S showed higher µstrain values for all simulated misfit levels. The type of implant did not affect the stresses around pillar P. Conclusions: Photoelasticity and FEA are reliable methodologies presenting similarity for the investigation of the biomechanical behavior of implant-supported rehabilitations.